MEDICINAL PLANTS- ANTIOXIDANT PROTECTIVE AGENTS AGAINST OXIDATIVE STRESS, RADIATION AND VIRUS INFECTION - Veselin Ivanov (Science & Research)

(untitled)
In this review, we strive to evaluate and provide sufficient evidence of the antioxidant and protective essence of classic herbs (Silybum marianum, Curcuma longa Linn, Haberlea rhodopensis Friv), used as dietary antioxidants, DNA modulating agents, metabolic radiation scavengers, hepatoprotectors, cancer treatment, and COVID-19 infection agents. The future use and development of effective herbal combinations require efficient non-toxic mixtures and conventional chemotherapeutics neutralizing systemic oxidative stress and predisposing to a reduced risk of developing cardiovascular, pulmonary, and neurodegenerative diseases, cancer, and etc.